Beyond Western cynicism: American Cognitive Warfare through an anti-hegemonic lens - Rocha, Isabela; Dashichev, Aleksandr (InterAção, 2025)
Mainstream accounts, both in the West and in parts of the Global South, consistently portray China and Russia as the principal actors behind Cognitive Warfare in contemporary conflicts (Wood and Kania, 2021; Cheravitch, 2020; VIGINUM, 2024a, 2024b; Fagins, Nacht and Chafetz, 2021). This article advances a counter-hegemonic perspective by returning to Paul Linebarger’s seminal Psychological Warfare (1948) to demonstrate that the conceptual and institutional foundations of Cognitive Warfare are not foreign inventions, but deeply rooted in American strategic thought. By tracing the genealogy of Psychological Operations from their Cold War codification to their digital transformation, we reinterpret Linebarger’s eight principles of PsyOps through the algorithmic infrastructures of social media. Our analysis highlights how practices such as audience targeting, emotional saturation, infrastructural control, and perpetual iteration have been rearticulated in the digital era, culminating in what we call Meta-Trumpismo: the fusion of state power with Big Tech infrastructures as a vehicle for 21st-century PsyOps. We argue that Cognitive Warfare should be understood not as an external threat but as the institutional maturity of US influence strategies, now embedded into global communication systems through the convergence of military doctrine, corporate platforms, and algorithmic governance.